تطبيق الإملاء المنقول لتنمية مهارة الكتابة لدى الطلاب المبتدئين في معهد نور الفلاح كمبانج تانجونج - Sanwil, Teuku (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
The objectives of this research were to understand the implementation process of imla’ manqul in enhancing beginner students’ writing skills at Nurul Falah Institute, Kampung Tanjung. The research method used in this study was action research. The tools employed by the researcher for data collection were observation, tests, and documentation. The results of the study, based on the action research conducted, revealed that the application of imla’ manqul to improve writing skills among beginner students at Nurul Falah Institute, Kampung Tanjung, was effective. The average score of students in the first cycle was 62, indicating the need for a second cycle. In the second cycle, the average score improved to 73.83. The teaching and learning process was effective, with students demonstrating increased engagement and enthusiasm during the lessons.